Spatiotemporal changes in temperature projections over Bangladesh using multi-model ensemble data - Islam, H. M. Touhidul; Kamruzzaman, Mohammad; Shahid, Shamsuddin; Mainuddin, Mohammed; Alam, Edris; Islam, Abu Reza Md. Towfiqul; Biswas, Jatish Chnadra; Islam, Md. Azharul (Frontiers in Environmental Science, 2023)
Temperature rise is a concern for future agriculture in different regions of the globe. Using 40 General Circulation Models (GCMs) of Coupled Model Intercomparison Project Phase 5 (CMIP5) for two radiative concentration pathways (RCPs, RCP4.5 and RCP8.5), the goal of this study was to find out how the minimum temperature (Tmin) and maximum temperature (Tmax) will change and vary over Bangladesh on a monthly, seasonal, and annual scale in the future. The statistical downscaling climate model (SimCLIM) was used for downscaling and to ensemble projections of temperature (Tmax and Tmin) changes for the near (2021–2060) and far (2071–2100) periods compared to the base period (1986–2005). The multi-model ensemble (MME) exhibited increasing Tmax and Tmin trends for all the timescales for both the periods and RCPs. Sen's slope (SS) analysis showed that both Tmax and Tmin were getting higher in February, but not as much as in July and August. The mean annual Tmax over Bangladesh is expected to rise by 0.61°C for RCP4.5 and 1.75°C for RCP8.5 in the near future, and by 0.91°C and 3.85°C in the far future. According to RCP4.5 and RCP8.5, the mean annual Tmin across Bangladesh is predicted to rise at a rate of 0.65 °C and 1.85 °C in the near future and 0.96 °C and 4.07 °C in the far future, respectively. A greater increase in the far future than in the near was observed in this study. Tmax and Tmin would go up the most in the northern and northwestern parts of the country, which have always been subject to temperature extremes. In contrast, the southeastern coastal region would experience the least rise in temperature. On all timescales, the increase in Tmin was greater than the increase in Tmax. This means that the DTR will go down in the future. The maximum and minimum temperatures will rise the most in winter compared to other seasons and RCPs. The changes in projected Tmax and Tmin can be useful for the region's long-term planning.